Does Financial Performance Determine A Going Concern Audit Opinion? An Empirical Study In Agriculture Industry - Rahmatullah, Nur; Syarif, Ahmad; Junaidi, Muhammad Ali (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Global economic uncertainty due to the US-China Trade War and the emergence of the COVID-19 pandemic has made many companies unable to maintain their business continuity. It raises concerns from investors, who believe the target company cannot provide optimal returns on their invested funds. As a result, investors tend to withdraw the funds that have been invested so that they do not experience unexpected losses. Therefore, researchers are interested in analyzing how much financial performance can influence the auditor in giving a going concern audit opinion. This study uses a quantitative approach, and the data is from the agriculture sub-sector companies listed on the Indonesia Sharia Stock Index. The sampling technique in this study used purposive sampling, resulting in 30 samples being analyzed using logistic regression. The study results prove that the solvency and profitability ratios influence the auditor in giving a Going concern audit opinion. Activity ratio does not influence the auditor in giving a Going concern audit opinion.